Prediksi Kebutuhan Hutan Kota Berbasis Oksigen di Kota Padang, Sumatera Barat - Septriana, Diana; Indrawan, Andry; Dahlan, Endes Nurfilmarasa; Jaya, I Nengah Surati (Institut Pertanian Bogor (IPB University), 2004)
The study describes a method for predicting urban forest area in Padang City based upon oxygen needs. The result shows that the needs of urban forest in Padang City increase continously, mainly due to the increase of industries. Since the year 2002, the spatial analysis also found that the significant increase of the urban forest need occurred in Lubuk Kilangan disctrict, i.e., approximately 368,88 hectares per year. In the year 2020, the estimate needs of urban forest in all Padang City are 14,894.61 hectares. This need is approximately 53% of the area. Furthermore, the extent of urban forest is still sufficient for supplying oxigen up to the year 2020. However, it is also the spatial analysis shows that urban forest (vegetated area) are not evenly distributed in the centers of economic activities (e.g. settlement, industries, shopping centre, etc). Key words : ,